A case report of isolated bone marrow metastasis from neuroendocrine tumor of occult primary: A pathologist's perspective on this unusual presentation - A case report - Pretty Singh; Kavita Somani; K Sujatha (Apollo Medicine)
Introduction: Neuroendocrine tumors (NETs) are poorly understood neoplasms that, although slow growing compared with epithelial malignancies, can behave aggressively. Bone marrow (BM) is an uncommon site of metastasis by neuroendocrine tumors (NETs), occurring in approximately 5% of the cases. Despite advanced diagnostic techniques, primary site cannot be deciphered in few patients. Case: A 46-year-old male with a recent history of myocardial infarction, rapidly worsening back pain from past two months. He was referred to us with a suspicion of multiple myeloma with multiple lytic lesions of bone. The patient underwent a BM examination, which revealed extensive infiltration of the marrow with tumor cells positive for immunohistochemical (IHC) markers of NET with high proliferation index. Thus, a diagnosis of “metastatic NET” was rendered. Conclusion: In an occult primary, a panel of IHC biomarkers are of key importance to confirm the nature and grade of the tumor. Site-specific markers may be lost in high-grade tumors. Thus, in an era of theradiagnostics, immunohistochemistry remains a tool of paramount vitality, to accurately classify these tumors, and may aide in finding the primary site of neoplasm.